The False Gods - Lorimer, George Horace, 1869-1937 (Salt Lake City, UT : Project Gutenberg, 2005)
"The False Gods" by George Horace Lorimer is a novel written in the early 20th century. The book explores themes of infatuation, deceit, and the intricate dynamics of personal relationships set against a backdrop of Egyptology and mysticism. It mixes elements of mystery, romance, and societal commentary within the framework of journalistic pursuits. The story centers around Ezra Simpkins, a reporter investigating the enigmatic Mrs. Athelstone, who is tied to the esoteric Royal Society of Egyptian Exploration. Initially seeking a sensational story involving her and a rival woman, Madame Gianclis, Simpkins finds himself drawn deeper into the secretive world of Mrs. Athelstone, where he unravels mysterious connections, encounters a mechanical statue of Isis, and ultimately discovers the unsettling truth about the death of her husband. As Simpkins grapples with his feelings for Mrs. Athelstone and the implications of his discoveries, he navigates the treachery of human relationships, journalistic ethics, and the powerful allure of secrets. (This is an automatically generated summary.)
Release date is 2005-11-06
E-text prepared by David Garcia and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net/) from page images generously made available by the Kentuckiana Digital Library (http://kdl.kyvl.org/)
Keywords: Fantasy fiction; Paranormal fiction; Journalists -- Fiction